(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Essay entered the Uzbek literature in the second half of the 20th century and developed as a genre. Dozens of beautiful examples of it have been created. The essay "Sharif Manzarlar" created by Sadriddin Salim Bukhari occupies a special place in Uzbek essay writing. In the essay, the ideas of patriotism, humanitarianism, and science are put forward. The article contains a study of these aspects.